The influence of bacterial vaginosis during pregnancy, the fetus and newborn - L. V. Maisuradze; F. U. Magaeva; D. K. Alborov (Кубанский научный медицинский вестник, 2014)
As a result of the research it was revealed that pregnant women with bacterial vaginosis change indicators immunologists, feto-placental complex, leading to complications of pregnancy, development of hypoxia, intrauterine infection, high maternal and perinatal morbidity.